Comparing environmental DNA collection methods for sampling community composition on marine infrastructure. (5th April 2023) - Alexander, Jason B.; Marnane, Michael J.; McDonald, Justin I.; Lukehurst, Sherralee S.; Elsdon, Travis S.; Simpson, Tiffany; Hinz, Shawn; Bunce, Michael; Harvey, Euan S.
Abstract: Broad scale monitoring of marine diversity is challenging, with many techniques limited to sampling only a small portion of the actual diversity present. For this reason, molecular methods, such as environmental DNA (eDNA) metabarcoding, are becoming increasingly popular, especially in locations that are logistically difficult to sample (for example, ports, offshore platforms and other restricted marine infrastructure). eDNA studies in marine environment have predominantly focused on the collection and isolation of DNA from water. Recent literature suggests this approach may not be effective for detecting taxa from adjacent epibenthic substrates. In this study we compare a visual, morphological approach utilizing three eDNA sampling methods targeting the water column and four methods targeting the epibenthic substrate: three methods scraping and one swabbing the epibenthos. Sampling was completed at two depths on and adjacent to a decommissioned jetty, with all methods detecting significant community compositions. Only 2.8% of family-level taxonomic detections were found across all eDNA sampling methods, and all but one scraping method were able to detect fine scale community shifts associated with depth. The epibenthic sampling methods ranged from 50 to 117 families detected, with those methods that collected bulk DNA material (all scraping methods) detecting considerably lower diversity. The methods targeting the water column detected between 78 and 154 families, with the polyurethane foam (PUF) tow method detecting the highest number of families, indicating that the physical matrix may be better at retaining traces of DNA within the water column. While further validation is required, this study provides a base toolkit for the broad characterisation of vertical diversity at both natural and man-made marine structures such as oil and gas platforms. Additionally, these highly varied results demonstrate the importance of appropriate substrate selection to sample for a given study objective and indicates that multiple sampling methods may be required to holistically characterise diversity across a chosen environment using eDNA. Highlights: Only 2.8% of family-level taxonomic detections were found across all eDNA sampling methods. Epibenthic methods detection ranged from 50 to 117 families, with methods collecting bulk organic material detecting lower diversity. Methods targeting the water column detected between 78 and 154 families. Increased eDNA concentration does not necessarily correspond to increased diversity.